Friday

April 18, 2014

April 18, 2014

Posted by **Tracy** on Wednesday, September 30, 2009 at 11:31am.

3(x6)-4>2(x+4)-3(6+5)<8(7-3)=

Answer:

3(x+6)-4>2(x+4)=

3x+18-4>2x+8=

3x+14>2x+8=

3x-2x>8-14=x>-6

Thank you.

- Algebra 1A -
**drwls**, Wednesday, September 30, 2009 at 11:57amIt makes no sense to me to have an equals sign folloing an inequality.

Are you supposed to turn the inequality into another inequality that tells you whatnumber x is greater or less than?

If 3(x+6)-4 > 2(x+4), then

3x + 18 -4 > 2x + 8

x + 14 > 8

x > -6

which agrees with your answer.

- Algebra 1B -
**shay**, Friday, December 17, 2010 at 9:21amnone

**Related Questions**

Algebra - Is this the right way to do this problem? 3(x+6)-4>2(x+4 -3(6+5)<...

math - solve for X ? 1) 8-3x < 14 -3x/-3 < 6/-3 x=-2 2) 7x -3 > 4x +3 ...

math, beginning algebra - how do i solve the following equations. Problem # 1 3x...

Math - can someone check to see if these inequality equations are the correct ...

advance algebra - 1. 2(6x+13)-7 >= 21 ">=" is greater than or equal 2. |...

Algebra - Please Solve: (x+3)(x-5) < 0 I got so far on this and am lost.. (x+...

math-slopes - >wat is an equation of the line that passes through the point (...

algebra - Solve for x. (l is the absoulte bar, not one) 3*l 3x-2 l -6 > l 3x-...

Math - 2x(5*2-3) > x(3-5)-2(x-1) the answer I have got is x > 2/18. Can ...

advance algebra - 1. 2(6x+13)-7 >= 21 ">=" is greater than or equal <= ...